Lunch breaks as a buffer: mitigating the negative effects of road traffic noise on urban employee workplace behavior - Ke, Jianglin; Wang, Zhaoyue; Zhang, Yufei; Liu, Lidan; Wang, Qiongwei (Frontiers in Public Health, 2025)
IntroductionThe impact of road traffic noise annoyance on individual health is well-documented in environmental and health studies. However, less attention has been given to its negative effects on employees’ work behaviors and effective mitigation strategies.MethodsDrawing on conservation of resources theory and general strain theory, this research conducted a three-wave survey involving 816 urban employees from 304 Chinese cities.ResultsThe results revealed a significant positive correlation between residential road traffic noise annoyance and employees’ mental health complaints, work withdrawal, and workplace aggressive behaviors. Mental health complaints were confirmed to fully and partially mediate the relationship between noise annoyance and work withdrawal and workplace aggressive behaviors, respectively. The organizational lunch break environment negatively moderates the link between residential road traffic noise annoyance and mental health complaints.DiscussionThese findings underscore the importance of addressing noise annoyance to enhance both employee welfare and organizational efficacy.